A reconstrução histórica do movimento de trabalhadores técnico-administrativos através da fotografia: o Sindicato dos Trabalhadores das Universidades Públicas Estaduais RJ (SINTUPERJ) - Benacchio, Rosilda Nascimento (2007)
The 90 s is characterized by the consolidation and late arrival of the neoliberal conception together with the Brazilian State. In the same decade, the principal the main international organisms recommended a redirection in the capitalists strategies and the incorporation of the third way politics. This project, in general lead by the new left s governments, is characterized by an efficient management of the capitalist acumulation through the state s reform which continues reducing rights and privatizing the public service. It is outlined the investment in an educacion for a new sociability proper to the old cenary of work s expropriation for the capital: a new hegemony s pedagogy. It is in the scenary that is developed our research about the moviment of the administrative-technician workers who are organized by the Union of the Works of the State Public Universities (Sintuperj), in the period of 2000 to 2006, specially through its photographies, oral history and other printed documental sources. This work intends to reflect on the realiy s analysis, the fights, victories and dificulties of this movement in front of the foregoing hegemony s pedagogy and its effects on the workers, wich are expressed just as inside the university as in the Union.